2022
DOI: 10.1186/s41938-022-00579-7
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiotic microbes from entomopathogenic nematode (EPNs) and their applications as biocontrol agents for agro-environmental sustainability

Abstract: Background The biological diversity on planet earth is declining day by day, due to different factors such as excessive applications of pesticides. The utilization of chemical pesticides affected environment as well as microorganisms. The awareness among the peoples towards the hazards by the residual toxicity of chemical pesticides should be developed for agro-environmental sustainability. Main body Entomopathogenic nematodes (EPNs) are the bacto-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 197 publications
0
14
0
Order By: Relevance
“…mouth, spiracles, cuticle and anus (Askary and Ahmad 2020). The juvenile stage along with its bacterial endosymbiont kills the insects efficiently through invading haemocoel by regurgitating endosymbiont (Tomar et al 2022b). These endosymbiont releases toxic compounds inside insect body, which finally kills the insects via toxaemia (Gaugler 2002).…”
Section: Introductionmentioning
confidence: 99%
“…mouth, spiracles, cuticle and anus (Askary and Ahmad 2020). The juvenile stage along with its bacterial endosymbiont kills the insects efficiently through invading haemocoel by regurgitating endosymbiont (Tomar et al 2022b). These endosymbiont releases toxic compounds inside insect body, which finally kills the insects via toxaemia (Gaugler 2002).…”
Section: Introductionmentioning
confidence: 99%
“…"Application of entomopathogenic nematode (EPNs) with their bacterial endosymbionts become a prime approach in the biocontrol sector as an ecologically safer tool in a sustainable agriculture perspective as well as in integrated pest management" [6]. "Since the early 1970s, there has been a tremendous research and commercial interest in entomopathogenic nematodes and their associated bacteria" [7].…”
Section: Inrtoductionmentioning
confidence: 99%
“…"Since the early 1970s, there has been a tremendous research and commercial interest in entomopathogenic nematodes and their associated bacteria" [7]. "In the 1990s and twentieth century's vast studies on EPNs were carried out, and it was reported that EPNs were distributed worldwide" [6]. (EPNs) exist widely in the soil.…”
Section: Inrtoductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also well-known beneficial parasitic nematodes that are used for biologic control of agricultural pests. Entomopathogenic nematodes (EPNs) are used in integrated pest management [ 9 , 10 , 11 ]. EPNs are also regarded as a model system and are widely used in evolutionary biology, biological control, symbiosis, soil ecology, and neurobiology [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%